Thermal Diffusivity Investigation of Turbine Jet Engine Compressor Blade Material by Modified Temperature Oscillation Method - Łukasz OMEN; Andrzej PANAS (Problemy Mechatroniki)
The modified temperature oscillation method was applied for investigation of thermal diffusivity of the aviation turbine engine’s part. The studies resulted in characterization of the applied method and experimental procedures performance. They were motivated by a need of determination of thermophysical data of the investigated material. The acquired thermal diffusivity data enabled identification of the material’s type and will be applied as input data for numerical analyses on thermo-mechanical loads of the structure. The investigated specimen was a sample of material from the first stage compressor’s blade of the AŁ-21F3 turbine engine. The measurements were conducted within the range of 5°C to 95°C. The thermal diffusivity was calculated from both the amplitude and phase responses to the harmonic excitation from exact analytical solution of the appropriate heat conduction problem. The appropriate transcendental equations describing the response signal amplitude attenuation and phase shift were solved applying iterative procedures. The analysis confirmed the effectiveness of the research methods and enabled to identify the material as titanium alloy.